(untitled) (Indian Journal of Public Health Research & Development, 2022)
Background: Lingual holding arch appliance has been the most trusted space maintainer in the field of pediatric dentistry. This study put forward mapping of application of various designs of lingual holding arch appliance and to verify the main gap in the research on this field. Methods: This is a scoping review that took place in 2021 following PRISMA-ScR Guideline. Data was searched through the database PubMed, SCOPUS, Google scholar The search strategy included keywords’ bilateral fixed space maintainer’ ‘space maintainer’ ‘lower lingual holding arch’ ‘fixed lingual arch appliance’ ‘functional lingual arch holding appliance’ A total of eleven studies from nine hundred and thirty original articles were identified and were included and reviewed. The study selection and tabulation of data were performed by two independent reviewers. Any disagreement in study selection was resolved by a third reviewer. Conclusion: In the transitional phase, preventive and interceptive orthodontic plays a significant role in minimizing the inevitable developing malocclusion The mapping determined all proposed designs for the prevention of space loss. Each design needs to be carefully selected based on the phase of mixed dentition. This paper provides information on various designs of a lingual arch space maintainer, and it can be concluded that there is a necessity for long-term follow-up studies for further research in the field.